2021
DOI: 10.22141/2224-0721.17.2.2021.230573
|View full text |Cite
|
Sign up to set email alerts
|

Цукровий Діабет І Артеріальна Гіпертензія

Abstract: This review article summarizes the existing literature on the current state of the problem of diabetes mellitus and arterial hypertension. According to the World Health Organization, hypertension and type 2 diabetes mellitus, after obesity, are among the leading cardiovascular risk factors that are most common among the world’s population. Over the past 30 years, the prevalence of hypertension has decreased to a quarter of the world’s population, but the incidence of diabetes mellitus has increased from 4.7 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…million hospitalizations and more than 300,000 deaths reported annually [1]. Current scientific data indicate that among the world's population, arterial hypertension (AH) and type 2 diabetes mellitus (T2DM) after obesity are among the leading factors of cardiovascular risk [2]. Studies have shown that improved glycemic control can reduce the progression and onset of microvascular complications [3].…”
mentioning
confidence: 99%
“…million hospitalizations and more than 300,000 deaths reported annually [1]. Current scientific data indicate that among the world's population, arterial hypertension (AH) and type 2 diabetes mellitus (T2DM) after obesity are among the leading factors of cardiovascular risk [2]. Studies have shown that improved glycemic control can reduce the progression and onset of microvascular complications [3].…”
mentioning
confidence: 99%